Historical anthropization of a wetland: steady encroachment by buildings and roads versus back and forth trends in demography. (March 2018) - Guetté, Adrien; Godet, Laurent; Robin, Marc
Abstract: Coastal wetlands have been deeply modified by humans over the last centuries. The assessment of such changes has been mainly documented through traditional Land-Use or Land-Cover (LULC) change studies, basically mapping changes in the composition of the main habitats. Through the example of the second largest wetland in France (the Marais Poitevin, 1000 km 2 ), our aim was to test whether only taking into account changes in habitat composition is sufficient to assess the anthropization of a wetland. For the first time at such a temporal and spatial scale and at such a spatial resolution, we documented the historical evolution of human demography, buildings and roads over the three last centuries in this area. These data were then compared with historical changes in habitat composition. We found that backward and forward temporal trends in habitat composition were linked with the evolution of human demography but that building and road density increased steadily over time. Consequently, remote areas far from human artifacts (buildings and roads) have become increasingly scarce. Our results suggest that to assess the anthropization of a wetland, not only changes in habitat composition should be taken into account but also every human artifact that can dramatically change a landscape. Highlights: In the Marais Poitevin trends in population are linked with back and forth trends in habitat composition. We found a steady increase in buildings and in roads over the three last centuries. Remote areas far from human artifacts (buildings and roads) have become increasingly scarce. This highlights the importance to better take into account the spatiotemporal dynamics of buildings and roads.